Helicopter type and accident severity in helicopter emergency medical services missions - Hinkelbein, Jochen; Schwalbe, Mandy; Wetsch, Wolfgang A.; Spelten, Oliver; Neuhaus, Christopher (Aviation, space & environmental medicine, 2011)
Hinkelbein J, Schwalbe M, Wetsch WA, Spelten O, Neuhaus C. Helicopter type and accident severity in Helicopter Emergency Medical Services missions. Aviat Space Environ Med 2011; 82:1148-52. - Objective: - Whereas accident rates and fatal accident rates - for Helicopter Emergency Medical Services (HEMS) were investigated sufficiently, resulting consequences for the occupants remain largely unknown. The present study aimed to classify HEMS accidents in Germany to prognosticate accident severity with regard to the helicopter model used. - Methods: - German HEMS accidents (1 Sept. 1970-31 Dec. 2009) were gathered as previously reported. Accidents were categorized in relation to the most severe injury, i.e., 1) no; 2) slight; 3) severe; and 4) fatal injuries. Only helicopter models with at least five accidents were analyzed to retrieve - representative data. Prognostication was estimated by the relative percentage of each injury type compared to the total number of accidents. - Results: - The model BO105 was most often involved in accidents (38 of 99), followed by BK117 and UH-1D. Of N = 99 accidents analyzed, - N = 63 were without any injuries (63.6%), N = 8 resulted in minor injuries of the occupants (8.1%), and N = 9 in major injuries (9.1%). Additionally, N = 19 fatal accidents (19.2%) were registered. EC135 and BK117 had the highest incidence of uninjured occupants - (100% vs. 88.2%) and the lowest percentage of fatal injuries (0% vs. 5.9%; all P > 0.05). Most fatal accidents occurred with the models UH-1D, Bell 212, and Bell 412. - Discussion: - Use of the helicopter models EC135 and BK117 resulted in a high percentage of uninjured - occupants. In contrast, the fatality rate was highest for the models Bell UH-1D, Bell 222, and Bell 412. Data from the present study allow for estimating accident risk in HEMS missions and prognosticating resulting fatalities, respectively.